Factors affecting cytological results of endoscopic ultrasound guided-fine needle aspiration during learning - Jian-Han Lai; Hsiang-Hung Lin; Ching-Chung Lin (BMC, 2020)
Abstract Background Endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) is a standard procedure used to obtain tissue samples for diagnosis of solid retroperitoneal tumours. However, this procedure demands high technical expertise and requires a strong learning curve. Our aim was to identify factors associated with false-negative EUS-FNA results during the learning for endoscopists. Methods Our retrospective analysis was based on the EUS-FNA specimens collected by two novice endoscopists in 200 patients with retroperitoneal lesions who had confirmed image- or tissue-based diagnoses of malignancy or benign lesions. Results In the first 40 performances endoscopists, the false-negative diagnostic rate of EUS-FNA was higher among patients with chronic pancreatitis than in patients without chronic pancreatitis. Patients who underwent FNA through the trans-duodenal puncture route also had lower success cytological diagnosis rate than through the trans-gastric puncture route. The rate of successful cytological diagnoses with EUS-FNA improved after 40 procedures and was not influenced by chronic pancreatitis presentation or difference puncture route. Conclusion Regarding the learning curve, more than 40 procedures were required to achieve a stable success rate of EUS-FNA. Chronic pancreatitis and trans-duodenal puncture route are the predictive factors for a false-negative FNA cytological result during learning. Trial registration This was a retrospective study.